Evaluation of activated carbon from waste tyre for the adsorption of 2-chlorophenol - Kanchana, Manirajah (2016)
A mesoporous carbon developed from waste rubber tire, characterized by chemical analysis where firstly reported with X-ray diffraction (XRD) indicating the presence of activated carbon and revealed a predominantly amorphous structure of the tire-derived activated carbon. Field Emission Scanning Electron Microscope (FESEM) images resulted in surface structure of the activated carbon. Fourier transform Infrared spectroscopy (FTIR) showed the presence of functional group. Hence, in this research activated carbon was used as an adsorbent for the removal of 2-chlorophenol. Surface area, porosity, and density were determined. The adsorption of the 2-chlorophenol over the prepared adsorbent was achieved under different adsorbate concentration, pH and adsorbent dosage. By percolating the 2-chlorophenol solution through UV–vis diffuse reflectance spectroscopy, the bulk removal of the chlorine was carried out and necessary parameters were determined to find out the percentage removal. The synthesized activated carbon as an effective adsorbent dosage for the removal of 2-chlorophenol due to its excellent stability and chemical inertness and is known to be biocompatible.